2021
DOI: 10.1084/jem.20202012
|View full text |Cite
|
Sign up to set email alerts
|

The histone demethylase Lsd1 regulates multiple repressive gene programs during T cell development

Abstract: Analysis of the transcriptional profiles of developing thymocytes has shown that T lineage commitment is associated with loss of stem cell and early progenitor gene signatures and the acquisition of T cell gene signatures. Less well understood are the epigenetic alterations that accompany or enable these transcriptional changes. Here, we show that the histone demethylase Lsd1 (Kdm1a) performs a key role in extinguishing stem/progenitor transcriptional programs in addition to key repressive gene programs during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 56 publications
11
12
0
Order By: Relevance
“…However, no YFP-positive thymic B cells were observed. Our data suggested that the B cells were unlikely trans-differentiated from T lineages, consistent with a recent work which also failed to induce myeloid, B cell, and NK cells from Lsd1-deleted thymic progenitor T cells in the OP9-DL1 system [22]. We supposed that they were stimulated by the abnormal upregulation of IFN-γ in the thymic environment after Lsd1-deletion.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, no YFP-positive thymic B cells were observed. Our data suggested that the B cells were unlikely trans-differentiated from T lineages, consistent with a recent work which also failed to induce myeloid, B cell, and NK cells from Lsd1-deleted thymic progenitor T cells in the OP9-DL1 system [22]. We supposed that they were stimulated by the abnormal upregulation of IFN-γ in the thymic environment after Lsd1-deletion.…”
Section: Discussionsupporting
confidence: 92%
“…Considering the similar frequencies of YFP + thymic NK cells in KO mice compared with control mice, we speculated it to be resulted from reactive hyperplasia but not transdifferentiation. Consistently, previous investigation also observed the increased B cells and NK cells in the thymus in Lsd1 / CD2-Cre mice, but not in Lsd1 / CD2-Cre DN thymocyte cultures on OP9-DL1 cells [22]. In summary, the observed increased number of other lineage cells is not caused by the trans-differentiation from T cells.…”
Section: Ablation Of Lsd1 In Early T Cells Leads To Thymic Atrophy An...supporting
confidence: 89%
See 3 more Smart Citations